2006
DOI: 10.1016/j.ijsolstr.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical form-finding of tensegrity structures

Abstract: A novel and versatile numerical form-finding procedure that requires only a minimal knowledge of the structure is presented. The procedure only needs the type of each member, i.e. either compression or tension, and the connectivity of the nodes to be known. Both equilibrium geometry and force densities are iteratively calculated. A condition of a maximal rank of the force density matrix and minimal member length, were included in the form-finding procedure to guide the search of a state of self-stress with min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 20 publications
(32 reference statements)
2
86
0
1
Order By: Relevance
“…Finally, Estrada et al [25] presented an algorithm which only needs information about the type of each edge and about the topology, but does not account for external forces. Then, the equilibrium geometry and force densities for each edge are iteratively calculated using rank constraints on both the stress matrix (Ω) and the rigidity matrix (R(p)).…”
Section: Formfinding Methodsmentioning
confidence: 99%
“…Finally, Estrada et al [25] presented an algorithm which only needs information about the type of each edge and about the topology, but does not account for external forces. Then, the equilibrium geometry and force densities for each edge are iteratively calculated using rank constraints on both the stress matrix (Ω) and the rigidity matrix (R(p)).…”
Section: Formfinding Methodsmentioning
confidence: 99%
“…Moreover, due to the principle that the struts withstand pressure and cables bear tension, if v b does not satisfy tension-compression symbols, it is necessary to add orthogonal vectors to reconstruct the force density ζ [7].…”
Section: Solution Of Elemental Self-stressmentioning
confidence: 99%
“…However, the procedure needs so many search steps that it requires much more computation time. It should be noted that Estrada et al [7], Tran and Lee [8] introduced a form-finding algorithm based on the iterative computation of force density and coordinate. The algorithm merely needs to provide the connections of cables and struts, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensegrities have applications in a range of fields such as sculpture, architecture, aerospace engineering, civil engineering, marine engineering and biology [7]. Most studies found in the literature investigated form-finding [8][9][10][11][12] and design characteristics of tensegrity structures [13][14][15][16]. Statics and dynamics of simple tensegrity modules have also been investigated [17][18][19].…”
Section: Introductionmentioning
confidence: 99%